Kajian kebutuhan ruang terbuka hijau sebagai penyerap emisi CO2 kendaraan bermotor di Ruas Jl. Drs. Esau Sesa - Erni; Raharjo, Syafrudin; Monim, Hanike (Cassowary, 2025)
ABSTRACT : Motor vehicle emissions have emerged as a significant global concern, adversely impacting air quality, human health, and environmental sustainability. In Indonesia, accelerated urbanization and the rising quantity of motor vehicles have exacerbated this issue, resulting in elevated carbon dioxide (CO₂) emissions. Vegetation is one of the most efficient natural solutions for reducing CO₂ pollution, as plants are essential for carbon sequestration by absorbing CO₂ from the atmosphere. This study aims to evaluate CO₂ emissions generated by vehicular operations and assess the CO₂ absorption capability along Drs. Esau Sesa Road to Trikora Arfai Manokwari Road. The quantitative research approach indicates that transportation activities on Drs. Esau Sesa Road produce approximately 20.843.795,10 kg/year of CO₂ emissions. Twenty-one tree species, comprising 136 individual trees, were discovered along the route. The total CO₂ absorption capacity of these trees is 140.740,00 kg/year, with Gersen (Muntingia calabura) demonstrating the greatest absorption potential at 56.286,86 kg/year. These findings highlight the significance of urban green spaces in alleviating air pollution and enhancing environmental quality. Enhancing afforestation initiatives and incorporating vegetation into urban planning are crucial measures for mitigating transportation-related emissions and fostering sustainable urban development. Future research should investigate supplementary techniques to augment CO₂ absorption capacity using various plant species and urban forestry programs.